Interlinking FinTech and eHealth: a qualitative study - Al-Anezi, Fahad (Frontiers in Public Health, 2024)
This study investigates the integration of financial technology (FinTech) and electronic health (eHealth) to explore the opportunities, challenges, and implications arising from their interlinkage in Saudi Arabia. Utilizing qualitative semi-structured interviews with 26 participants-including physicians, patients, technical and administrative managers, and FinTech consultants-the research adopts an inductive approach to understand diverse perspectives. Key findings reveal significant benefits such as improved efficiency in administrative processes, enhanced access to healthcare services, increased financial inclusion, better decision-making, improved patient experience, and the promotion of innovation and sustainability. However, barriers including regulatory challenges, data privacy and security concerns, interoperability issues, the digital divide, resistance to change, and cost implications were also identified. Overall, the integration of FinTech and eHealth holds substantial promise for advancing healthcare delivery in Saudi Arabia. Future implications include the expansion of telehealth services, an increase in startups, the integration of wearable health devices, blockchain-based systems, evolving regulatory frameworks, and heightened collaborations.Addressing the identified challenges is crucial for realizing the full potential of this integration.